2015
DOI: 10.1200/jco.2015.33.7_suppl.408
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of sunitinib and gemcitabine in sarcomatoid and/or poor-risk patients with metastatic renal cell carcinoma.

Abstract: 408 Background: Sarcomatoid renal cell carcinoma (sRCC) is associated with aggressive biology and poor prognosis. Poor-risk RCC, as defined by established risk factors, demonstrates similar aggressive behavior. Though vascular endothelial growth factor (VEGF) therapy is the standard initial therapy for RCC, insufficient data exist in sRCC and efficacy is limited in poor-risk disease. The objective of this study was to investigate the efficacy of anti-angiogenic therapy and cytotoxic chemotherapy in clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4 Initial studies involving vascular endothelial growth factor (VEGF) inhibitors have not demonstrated improvement in survival 3 ; however, a recent phase II study of sunitinib with gemcitabine demonstrated an overall response rate (ORR) of 26% with a stable disease rate of 38%. 5 Several reports have suggested that sRCC tumor cells express programmed cell death ligand 1 (PD-L1) more frequently when compared with clear cell tumors. 6 7 This likely reflects a more inflamed milieu within sRCC, since PD-L1 upregulation is known to result from the presence of type II interferons within the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…4 Initial studies involving vascular endothelial growth factor (VEGF) inhibitors have not demonstrated improvement in survival 3 ; however, a recent phase II study of sunitinib with gemcitabine demonstrated an overall response rate (ORR) of 26% with a stable disease rate of 38%. 5 Several reports have suggested that sRCC tumor cells express programmed cell death ligand 1 (PD-L1) more frequently when compared with clear cell tumors. 6 7 This likely reflects a more inflamed milieu within sRCC, since PD-L1 upregulation is known to result from the presence of type II interferons within the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Sunitinib and gemcitabine were well tolerated [57]. Furthermore, poor-risk mRCC patients receiving sunitinib in combination with gemcitabine in a Phase II study achieved an ORR of 24% and a median OS of 15 months (95% CI: 9-29) [58].…”
Section: Use Of Therapies Other Than Temsirolimus In Poor-risk Patientsmentioning
confidence: 94%
“…2 The primary endpoint of objective response rate (defined by Response Evaluation Criteria In Solid Tumors [RECIST] criteria) was achieved by 26% (n/N = 10/32) of evaluable patients. The stable disease rate was 38%.…”
Section: Potential Benefit Of Combined Vegf Inhibition Sunitinib and mentioning
confidence: 99%